AREAS OF IMPLEMENTATION OF INNOVATION MEASURES ON THE GAS DISTRIBUTION ENTERPRISES OF THE WESTERN REGION (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article is devoted to the analysis of the state of gas distribution companies in the western region of Ukraine and the need to implement innovative measures at these companies, since the organizational system of regional gas pipelines is characterized by significant static, conservative, the absence of separate innovative units, and there is а weakened focus of traditional units on the implementation of separate functions related to innovation and investment. The purpose of the article is to investigate innovative policy measures and ways of their implementation at gas distribution companies in Western Ukraine.The preconditions of forming an effective mechanism for managing innovation and investment activity at gas distribution companies are the theoretical provisions and practical recommendations we have proposed for: 1) existing innovations (innovative business processes); 2) the dualities of private investment capital; 3) flexibility of gas distribution tariff.The concept of existing innovations involves the widespread use of innovations that cover the entire range of business processes of the enterprise, the priority of which is the improvement of activities in order to choose a vector of orientation for consumers of gas services, and which are aimed at achieving the synergistic effect of the enterprise due to the impact of increasing the efficiency of all its functional units.The duality of innovation-investment capital at gas-distributing enterprises implies the creation of a complex of both internal (at the enterprise level) and external conditions for attracting such capital in order to solve the problems of innovative development by partial (spot, selective) privatization of existing gas-distributing capacities within the existing enterprises, which require major overhaul, modernization, technical re-equipment, as well as the creation of new logistic and distribution facilities.Practical implementation of the approach on the unification of distribution tariffs makes it possible to form a mechanism for the distribution of the total tariff revenue received by gas distribution companies or the gas transmission system operator between the entities in proportion to the volume of services provided or to individual components of these services, or on other bases that do not contravene the current legislation.The effectiveness of measures we proposed will allow us to implement organizational-managerial, technological, financial, personnel innovations in the activities of gas distribution companies in order to overcome the negative trends associated with their entry into the stage of decline and change their development vector with a focus on innovation.
Keywords: innovation, gas distribution enterprises, organizational and economic system, innovation and investment activity, effective innovations, duality of innovation and investment capital, microeconomic level, macroeconomic level, mesoeconomic level.